Soil monolith construction: a practical teaching experience for field and lab - (:unkn) unknown (My University, 1975)
Soil formation, structures and differences are difficult to visualize or understand without being able to experience them. Most of us are familiar with the soil profiles (soil sequum) on display in many Soil Conservation Service or County Extension Service offices. Whether an ecologist, engineer, or home gardener, we have all examined the intricate structures, features and horizon development. The objective of this paper is to describe a technique to construct such soil monoliths for classroom use with minimal expense.
Keywords: soil monolith; teaching